‘Chemlali Mhassen’: New olive cultivar derived from crossbreeding program in Tunisia with high oil quality and productivity - Guellaoui, I.; Amar, F. Ben; Triki, M. A.; Ayadi, M.; Boubaker, M. (Journal of Scientific Agriculture, 2021)
The new olive cultivar ‘Chemlali Mhassen’ was derived from the autopollination of the Tunisian oil cultivar ‘Chemlali Sfax’. The main morphological differences between the two cultivars were observed on the endocarp (symmetry, position of maximum diameter, apex, base and surface). On the agronomic plan, this cultivar is distinguishable from the original cultivar due to its medium earliness of bearing (4 years), medium alternate bearing (0.44), early ripening, moderate sensitivity to verticillium and its high olive production per tree (7.7 kg). Concerning oil quality, ‘Chemlali Mhassen’ had higher performances than the original cultivar for oleic acid content (70 to 77 %) and lower contents for palmitic acid (9.2 to 11.5 %) and linoleic acid (9.3 to 14.7 %). Similar performances were recorded between the new and the original cultivars for rhizogenesis behavior and pollen compatibility.